Evaluation of Ovsynch Protocol on Reproductive Performance of Anestrous Buffaloes during Breeding Season in Chitwan, Nepal (Nepalese Veterinary Journal, 2017)
This study evaluated the effectiveness of Ovsynch/FTAI protocol (day 0 fertirelin inj. 100μg I/M, day 7 cloprostenol inj. 500μg I/M, day 9 fertirelin inj. 100μg I/M, and day 10 fixed time artificial insemination 18 hours after second injection of fertirelin) in anestrous buffaloes of Chitwan, Nepal (n=14). Protocol was evaluated in terms of estrus characteristics, ovulation and pregnancy rate. Responses were analyzed by grouping the buffaloes based on type of anestrus, length of anestrus, body condition score (BCS), milking status, parity, age, management condition, follicle count on day of second GnRH treatment and site of semen deposition. Intensity of estrus characteristics on day of AI was mild. Major estrus signs observed were uterine tonicity, alertness, mucus discharge on rectal manipulation of internal genitalia, swelling of vulva and teat engorgement. Mucus discharge on rectal manipulation of internal genitalia and teat engorgement were clearly noticed in 50 % buffaloes. There was higher tendency (P=0.08) of estrus expression by buffalos with anestrous period of 10 months or lower compared to those with anestrous period longer than 10 months. Overall ovulation rate was 85.7%. Pregnancy rate to FTAI was 28.6% (22.2% and 40% in true anestrous and silent estrus buffaloes). 64.3% (66.7% and 60% of true anestrous and silent estrus) buffaloes were pregnant when checked at 102 days of FTAI including subsequent breeding. Although Ovsynch/FTAI seems to be alternative breeding technique in silent estrus buffaloes, further study with increased sample size is recommended. This protocol can potentially be used for resumption of ovarian cyclicity in true anestrus buffaloes.